Micropatterning of bioactive glass nanoparticles on chitosan membranes for spatial controlled biomineralization - Luz, Gisela (2011)
[Excerpt] Objectives: Chitosan membranes were patterned with bioactive glass nanoparticles (BG-NPs) capable of bone regeneration by a Microcontact Printing technique, in order to spatially control biomineralization and also cell adhesion and proliferation. [...]